Hardcore Music as a Medium for Social Critique and Cultural Resistance: An Ethnographic Study of the Surabaya Hardcore Community (SBHC) - Ririn Puspita Tutiasri; Sigit Andrianto; Jimmy Pradana (Lavish Opulent Education, 2025)
This study aims to examine how Hardcore music is utilized by the Surabaya Hardcore Community (SBHC) as a medium of social criticism and a form of resistance against various forms of domination, including those exerted by the state, institutions, and mainstream culture. As a subculture, Hardcore music has evolved not only as a form of musical expression but also as a symbolic act of defiance against dominant values perceived as oppressive.This research employs a qualitative approach using ethnographic methods, including in-depth interviews, participant observation, and focus group discussions, to understand the cultural practices, symbolic meanings, and social dynamics within the SBHC community.The findings indicate that Hardcore music plays a crucial role in shaping the community’s collective identity and in conveying socio-political messages. Lyrics addressing issues such as social injustice, oppression, poverty, and critiques of capitalism serve as key tools for voicing dissent and building collective awareness. Moreover, the SBHC community demonstrates strong solidarity through various social and collaborative activities, utilizing music as a means to strengthen social ties and expand networks of resistance.Music is not merely regarded as a form of entertainment, but as a powerful medium of cultural communication to express resistance, advocate for alternative values, and challenge the hegemony of popular culture. This study highlights how music subcultures like Hardcore provide a significant articulatory space for the pursuit of freedom of expression and social justice.